Soil macroporosity, physical properties and nutrient leaching after forest conversion to rubber and oil palm plantation in an Acrisol of Jambi, Indonesia - Sri Rahayu Utami; Syahrul Kurniawan; Christanti Agustina; Marife De Corre (Brawijaya University, 2021)
Soil degradation is expected to continue as forest conversion into other land uses increases significantly. In Indonesia, Jambi is one of the main areas for the development of oil palm and rubber, whichare mainly converted from the forest. As a base for better management, we attempted to study macro-porosity in rubber and oil palm plantation, in comparison to secondary forests. Four landuse systems (secondary forest, jungle rubber, rubber plantation and oil palm plantations) in Bukit Duabelas, Sarolangun District, Jambi Province, Sumatera, were selected for this study. The number of macropores in vertical or horizontal planes and their related factors (root mass, litter thickness, % organic C, bulk density, water content at pF 0 and pF 2.54, aggregate stability) were measured within the soil profiles. Forest conversion to jungle rubber, rubber and oil palm plantation led to a decrease of macro-porosity in the soil profile, especially in the upper 50 cm. Macropores, both at vertical and horizontal planes in the secondary forest was significantly higher than other landuses. Horizontal macropores in jungle rubber were higher than rubber and oil palm plantation, but not the vertical macropores. Among the soil properties measured, litter thickness, coarse root dry mass (Ø >2 mm), mesopores and aggregate stability were closely associated with soil macro-porosity. However, macro-porosity in the soil profile was insignificantly correlated to soil bulk density and % organic C. Increasing the number of horizontal macropores resulted in higher nutrient leaching, especially K and Na.